(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to shed light on intellectual property rights because of their importance and impact in increasing the revenues of the economic unit. Accordingly, the research sought to explain the imposition of income tax on intellectual property rights and its impact on the tax revenue. The research community was represented by the General Authority for Taxes, and the research sample was represented by a number of workers in The General Authority for Taxes and in various locations. As for the method adopted in the research, the researchers used the questionnaire as a tool of scientific research to demonstrate the extent of awareness of employees in the General Authority for Taxes about the imposition of income tax on intellectual property rights and its impact on the tax proceeds. Sixty-seven questionnaires were distributed and the data was analyzed using SPSS program One of the most important conclusions reached by the researchers was the existence of a significant relationship between imposing a tax on intellectual property rights and tax revenues, which contributes to increasing the state’s general budget revenues as well as distributing the tax burden, which achieves justice as one of the goals of sustainable development